An empirical study of social network addiction among students / Ahmad Shahir Jantan - Jantan, Ahmad Shahir (2016)
Nowadays there are lots of social networking sites found in the internet such as Facebook, Twitter, Google+ and moreover. Young people is the most exposed group to social network that influenced by modern trend. Social networks has many functions started through communicating with family and friends, playing games, online shopping, and also entertainment such as (YouTube etc). The negative consequences of social network addiction have been detected increasing recently. Although advanced technology is quite crucial but addiction to social network can affect human's health along with social imbalances and academic performance especially among the students. This research was conducted to study the level of social network addiction and the relationship among social network addiction among student to health and academic performance. A survey questionnaire was used to get the factor that effect of social network addiction and the relationship between social network addiction towards academic performance and health. Moreover, this survey will help to prevent users from highly addicted to their social network. However, due to limited time this research is conducted among college students and focus on the effect of social network addiction to academic performance and health. A questionnaire survey is gathered based on the literature review analysis of designing the good and related questionnaire. Data from, the result is inserted into SPSS to give the summary and measurement for each individual data. Students that use social network more than 2 years as targeted participant, help a lot in this research to get results from the survey. From this research the expected result is students able to know their level of social network addiction and the effect of social network addiction towards health and academic performance.